Pemanfaatan Laba dan Arus Kas dalam Memprediksi Kondisi Financial Distress - Nur Hafida; Achmad; Roni Yanto (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2025)
The development of science, technology, and communication that was increasingly advanced can have an impact on the economic competition of companies. The need for funds that were not small must be able to anticipate internal and external problems. Financial distress conditions can occur at any time in every company. One way to find out the condition of the company was to analyze the company's financial ratios and find out profit information as a basis for decision making for investors. In terms of investing in shares, cash flow information is the basis for decision making for creditors and for providing loans to companies. This study aims to test the effect of profit and cash flow on financial distress conditions in property, real estate and construction sector companies listed on the Indonesia Stock Exchange in 2020-2023. The research data used secondary data from the official website of the Indonesia Stock Exchange in the form of the company's annual financial report for 2020-2023. The research sample was taken using a purposive sampling technique. The data analysis method was in the form of quantitative analysis using logistic regression analysis. Hypothesis testing used SPSS Statistics 26 software. The results of the Hypothesis Test revealed that profit measured using the gross profit margin ratio has a significant effect on financial distress conditions. Meanwhile, profit is measured using the net profit margin ratio, return on assets, and return on equity do not have a significant effect on financial distress conditions. While profit was measured using the net profit margin ratio, return on assets, and return on equity do not have a significant effect on financial distress conditions. Cash flow was measured by the operating cash flow ratio, cash coverage ratio to current liabilities, capital expenditure ratio and total debt ratio do not have a significant effect on financial distress conditions.